IEEE GLOBECOM 2007-2007 IEEE Global Telecommunications Conference 2007
DOI: 10.1109/glocom.2007.697
|View full text |Cite
|
Sign up to set email alerts
|

PiggyCode: A MAC Layer Network Coding Scheme to Improve TCP Performance Over Wireless Networks

Abstract: In this paper we propose PiggyCode, a networkcoding based scheme specifically designed to enhance TCP performance over IEEE 802.11 multi-hop wireless networks. The root of this approach is a network coding module operating between the Network and the MAC layer. Each node running PiggyCode encodes, whenever it is possible, TCP-DATA and TCP-ACK packets belonging to the same information flow. The coding approach is conceptually analogous to piggyback the TCP-ACK packet within the TCP-DATA packet, with the substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
21
0
6
Order By: Relevance
“…Although the previously mentioned works [85][86][87][88][89][90][91][92][93][94][95][96] showed NC capabilities in TCP communications and improved the throughput of network, they can lead to a myriad of insecurity issues that should be handled. One of the most important security attacks in transport network layer, which is due to TCP connections, is Synchronization (SYN) flooding attack.…”
Section: Syn Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the previously mentioned works [85][86][87][88][89][90][91][92][93][94][95][96] showed NC capabilities in TCP communications and improved the throughput of network, they can lead to a myriad of insecurity issues that should be handled. One of the most important security attacks in transport network layer, which is due to TCP connections, is Synchronization (SYN) flooding attack.…”
Section: Syn Floodingmentioning
confidence: 99%
“…In 2007, [87] proposed a MAC layer NC scheme to improve TCP performance over wireless networks. Some works modified the traditional MAC layer for further improvements in coding gain [88].…”
Section: Syn Floodingmentioning
confidence: 99%
“…Scalia et al [17] suggested PiggyCode which allows the MAC to combine TCP data with TCP ACK by using network coding technology. This approach can reduce the MAC and PHY header overheads for TCP ACKs, similar to our approach.…”
Section: Related Workmentioning
confidence: 99%
“…There have been cross-layer approaches to improve TCP performance by piggybacking small TCP ACKs with link-level frames [14,19,20,17]. Parsa et al [14] proposed the transport unaware link improvement protocol (TULIP) that provides a piggyback method which transfers a TCP ACK with a link-level frame.…”
Section: Related Workmentioning
confidence: 99%
“…But it was shown in [9] that the performance gain of TCP with COPE in a 802.11 network can be neglected. A lot of research has been done on jointing implementation of TCP and network coding such as [10]- [12]. However, as we know, no attention has been paid to the performance degradation of TCP caused by the rate control mechanism of TCP itself and the routing protocol [8], [13], [14] has not been noted.…”
Section: Introductionmentioning
confidence: 99%